Systematic Literature Review: Multiple-tier Diagnostic Instruments in Measuring Student Chemistry Misconceptions - Muthmainnah Damsi; Slamet Suyanto (Jurnal Penelitian Pendidikan IPA, 2023)
Misconception is a conception of someone who is not by scientific concepts recognized by experts. One way to identify students' misconceptions is by conducting tests using diagnostic instruments. This study aims to identify misconceptions in chemistry learning as well as the most widely used types of multiple-tier diagnostic instruments. The research method used is a systematic literature review (SLR) by analyzing relevant research results from the Google Scholar and ERIC databases of 47 articles based on their suitability with the research theme within the last seven years (2016-2022). The systematic literature review method reviews articles systematically by following the steps that have been determined. The research findings show that students' misconceptions mostly occur in the buffer solution material with the most widely used diagnostic instrument, namely the three-tier multiple-choice (50%). The dominant cause of students' chemical misconceptions occurs due to students' internal factors in the form of a mismatch between students' preconceptions and the concepts taught by experts and strategies for applying learning models that are often used as a method to reduce students' chemical misconceptions such as the application of the Dual Situated Learning Model (DSLM) as well as implementing the Elicit, Confront, Identify, Resolve, Reinforce (ECIRR) model.